NILAI-NILAI MORAL DALAM LEGENDA GUNUNG BROMO - Sudar wati; Anik Cahyaning R. (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2016)
Abstract. The Bromo legend belongs to oral literature or folklore of the Tenggerese in the Situbondo Regency, East Java. The legend functions as a means of transmitting social values, a projection of social wishes, a tool of spreading religious teachings and a tool of law enforcement. The present study assumes that the Mount Bromo legend is aimed to teach moral values. This paper discusses the characters and the moral values in the Mount Bromo legend. Here the characters play the strategic positions as the messengers of the moral values to be delivered to readers. The study adopts philosophical-moral approach. The data source is the Mount Bromo folklore. The data collection methods include documentary, interview, recording, and note-taking methods. The data are collected using human instrument. The result of the study are as follows. The protagonists in the Mount Bromo legend are Rara Anteng, Joko Seger, and Kusuma, while th antagonist is Bajak. The moral values in the story are true love, just and wise ruler who listens to his people, religious ruler, loving parents and willingness to sacrifice for family and people.Keywords: protagonist, antagonist, moral values